Spatiotemporal characteristics and multi-scenario simulation of land use change and ecological security in the mountainous areas: Implications for supporting sustainable land management and ecological planning - Quan Wang; Xuepiao Bai; Dandan Zhang; Haijun Wang (Sustainable Futures, 2024)
The acceleration of global urbanization has intensified land use activities, which threaten the ecological environment and hinder the achievement of sustainable socioeconomic development goals. With the background of continuous land use expansion, the reasonable management of land use and ecological protection has increasingly become an important issue. This study constructs an ecological security (ES) index to evaluate the ES pattern, and employs the Future Land-Use Simulation (FLUS) model for multi-scenario simulation of land use patterns in mountainous areas. The results showed that from 2000 to 2020, cultivated land and grassland showed a sharp decrease, with areas of −128.64 and −228.18 km² respectively, while forest land, urban land, and other construction land increased, with areas of 116.12, 31.21, and 120.69 km² respectively. Over time, the mountainous areas mainly exhibited low and moderate ES patterns. Furthermore, for 2020–2030, under the natural development scenario, cultivated land, forest land, and grassland will show a decrease, while urban and other construction land will show a sharp increase. In contrast, under the ecological protection scenario, ecological land will show significant increase, and the patch expansion of urban construction land will be smaller. These results confirm the positive contribution of ES protection effects to improving the land use development, and support insightful guidance for formulating policies on ecological management in mountainous areas.